BALANCING VIRALITY AND PROCEDURAL JUSTICE: LAW ENFORCEMENT CHALLENGES IN THE INDONESIAN DIGITAL ERA - Muksin, Muchlas Rastra Samara; Suprihanto, Agus; Musashi, Ota (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2026)
The digital era has significantly transformed the dynamics of law enforcement in Indonesia, particularly through the widespread use of social media. The phenomenon of “No Viral, No Justice” illustrates a growing trend where public pressure via social media accelerates legal processes, whereas cases lacking online attention often face delays or neglect. This study examines how social media virality influences criminal case handling, highlighting both normative and empirical dimensions of justice. Drawing on doctrinal legal research, statutory analysis, and case studies, the research identifies the paradox inherent in digital oversight: while virality can enhance transparency and accountability, it may also compromise the principles of due process, presumption of innocence, and equality before the law. The study reveals that the spread of information on digital platforms can shape public opinion, sometimes creating trial by media, misinformation, and populist pressure, which can distort substantive justice. Furthermore, virality often favors emotionally charged or dramatic cases, producing a hierarchy of attention that undermines equitable access to justice. To address these challenges, the study recommends integrated digital reporting systems, objective case prioritization based on urgency and impact, ethical guidelines for communication, and strengthening the professionalism of law enforcement. By balancing public participation with procedural integrity, the legal system can leverage social media as a tool for oversight without sacrificing fairness or judicial independence. This research contributes to legal scholarship by providing an operational analysis of the interaction between digital social control and criminal justice, emphasizing the need for adaptive policies that preserve fundamental legal principles while accommodating the realities of the digital public sphere. Ultimately, the findings underscore that justice should remain a guaranteed right for every citizen, independent of the popularity of cases in the digital space, ensuring fairness, transparency, and accountability in law enforcement.